MANAJEMEN KONFLIK KEPERAWATAN DI TATANAN KLINIS: STUDI LITERATUR - I Made Moh. Yanuar Saifudin; Hasniah Dina; Ina Laela Abdillah; Josepha Mariana Tamaela; Lusi Anika (Universitas Kusuma Husada Surakarta, 2021)
Conflict is understood as an authentic part of life, which is sure to occur in all spheres of work, that work relations will be bad. To make a more conducive work atmosphere, a strategy is needed to manage conflict especially for conflicts in clinical settings involving various parties including the possibility of health workers. The literature review was conducted in electronic database including ScienceDirect, PubMed, and Sage Journals using a combination of search terms “Conflict Resolution AND Clinical Setting AND Hospital AND Nursing”. The result of this study said that conflict is one of problem that often occurs in any organization, for especially in the realm of the Hospital, which refers to an aggressive struggle to get the desired results and inhibit the achievement of others caused by several factors such as personality differences, values, limits unclear work, competition, decision making, poor communication. The way to overcome conflicts is accommodation by allowing other parties to get involved in problem solving, joint struggles in overcoming collaborative conflicts or actively seeking personal gain, but not bypassing and harming the interests of others. There are several factors that influence the success of overcoming Conflict in Clinical Settings, namely transparency, communication, listening and understanding.